Help desk system in i-Learn portal an enhancement - Wahab, Mazni (2006)
New information and communication technologies (ICT) allow learning "far away" from the teaching source. Nowadays e-Learning is a new learning methods growing significantly with the development of Information Technology. E-Learning is first and foremost about learning. The definition of e-Learning is very broad and generally refers to 'learning in a way that uses information and communication technologies'. The term e-learning is most frequently used to refer to computer-based training which incorporates technologies that support interactivity beyond that which would be provided by a single computer. I-Learn Portal is a new vision and approach implemented by UiTM that uses a range of learning technologies and media to integrate e-learning into its courses. E-learning on i-learn Portal, therefore, is an approach to facilitate and enhance learning thru, and based on, both computer and communications technology. It is believed that the real importance and significance in e-learning lies in its potential (Posiah Mohd Isa, 2005). To survive in the highlights competitive advantage, it is apparent that UiTM needs to provide user with the high quality services. The objective of this research is to identify the problem students face while using I-Learn and to enhance features of online help desk system in I-Learn Portal. Data is collected through the questionnaires and web observation. The web observation was considered of E-Learning institution web that affords help desk system services. Respondents was selected based on three criteria that were, they must UiTM student, user of I-Learn Portal and know the existence of help desk system. Through the analysis that has been done regards to the features, it shows that help desk in the I-Learn Portal still need to improve its features. The data that had been collected were analyzed by using SPSS Version 12.0 and Microsoft Office Excel.